Pandangan Sosiologis Politik terhadap Hak Veto PBB: Penolakan terhadap Gencatan Senjata Permanen dalam Konflik di Gaza - Farah Salma Rubbiyanti; Fawwaz As’ad Rizqullah (Universitas Islam Balitar, 2025)
The prolonged conflict in Gaza has raised global concerns, particularly regarding the role of the UN and the use of veto power in addressing the conflict. This article aims to critically examine the use of the UN veto power, especially regarding the rejection of a permanent ceasefire in the Gaza conflict, from sociological view of politics. Using a qualitative approach and analyzing primary and secondary literature, this article highlights the negative implications of the UN veto power and its ethical criticisms in the context of the Gaza conflict. The analysis results show that the Islamic political ethics perspective emphasizes the importance of justice, equality, and recognition of human rights in resolving the conflict. In conclusion, a sustainable solution to the Gaza conflict should involve active participation from the international community, reform of the world security system, and recognition of the basic rights of the Palestinian people.